The micro-processes of supplier satisfaction: A longitudinal multiple case study. Issue 4 (October 2021) - Weller, Sigrid B.M.; Pulles, Niels J.; Zunk, Bernd M.
Abstract: Supplier satisfaction has often been argued to be an important determinant for supplier performance in the buyer-supplier relationship. The micro-processes of how supplier satisfaction develops and how it relates to supplier performance, however, are not well understood. By means of a longitudinal multiple case study design of 18 buyer-supplier relationships, this paper provides insights into the micro-processes of how supplier satisfaction develops. Our findings provide several new insights. First, we observed how supplier satisfaction levels showed little change even though the buyer's behavior did not align with the supplier's expectations, thereby nuancing current conceptualizations of supplier satisfaction being a function of expected and realized relational value. Second, we show how intra organizational dynamics at the supplier influence the relationship between supplier satisfaction and supplier performance. Third, our findings give insights into the complex interplay between the relational and economic antecedents of supplier satisfaction. Highlights: This study presents the micro-processes of supplier satisfaction development Supplier satisfaction is not always a function of only expected and realized value Intra firm dynamics influence how supplier satisfaction relates to performance Relational and economic antecedents of satisfaction have a complex interplay